Assessment of occupational personal sound exposures for music instructors. Issue 3 (8th January 2021) - Crawford, Kathryn; Fethke, Nathan B.; Peters, Thomas M.; Anthony, T. Renée
Abstract: Daily activities performed by music instructors generate high sound levels that could potentially lead to overexposure. Adverse outcomes associated with high-exposure to sound, such as hearing loss and tinnitus, can be especially devastating to music instructors as hearing is essential to both job performance and career reward. The primary objective of this study was to compare sound exposures of music instructors to recommended exposure limits. Secondary objectives were to identify high-exposure activities and to evaluate potential similar exposure groups by examining between- and within-worker exposure variability. Personal sound exposure measurements from music instructors were collected using dosimeters during full workdays for up to 4 weeks over multiple semesters at a university's school of music. Study participants completed an activity log to record work-related activities throughout each day of sampling. Dosimeters logged 1-sec sound equivalent levels in A-weighted decibels. These data were used to calculate 8-hr time-weighted averages, daily dose, and activity-specific contributions to that dose to determine if daily exposures exceeded the recommended limit of 85 dBA and to identify high-exposure activities that could be targeted for future intervention. Seventeen participants were sampled for a total of 200 days. Approximately one-third of daily exposures exceeded recommended limits. The groups with the highest exposures were brass and conducting instructors. Conductors experienced the highest between-day variability in daily exposures. Activities that contributed the most to daily dose included group rehearsals, personal practice sessions, and performances, while classes and administrative work did not substantially contribute to daily dose. Daily exposures were highly variable, ranging from 60–95 dBA (mean = 81 dBA, sd = 8 dBA), and were influenced by instructional area and musical activity. Future exposure assessments for music instructors should include sampling for multiple days, and those above-recommended limits should be placed into hearing conservation programs.